Fonctionnement De La Plage d’El Jadida (Côte Atlantique Marocaine) : Apport De L’étude Morphodynamique, Sédimentologique, Minéralogique Et De L’action Anthropique - Soukaina Khouaja; Mohamed Ouadia; El Mehdi Irzan (European Scientific Journal, ESJ, 2016)
The multidisciplinary study of the beach of El Jadida and its sediments reflects that its shape is asymmetrical, narrow and contrasting between SE and NW which closely affects marine and wind dynamics and functioning of this beach. As profiles of beaches and the extension of the area affected by the tides, they present an argument for the elevation of the sea level had certainly warming. In addition to the Cretaceous lime stone be drock, the Quaternary calcarenites localized only in the SE richer, even more, this place in carbonate more than elsewhere in particular in winter. El Jadida beach sediments are basically homogeneous and well classified (coarse and fine) and reflect a more or less closed environment. The rocks of the SE affect the marine dynamics in rendering the texture of coarse and slightly heterogeneous sediments especially in winter but the correct classification is on the side fine sediments. The emitting provinces of minerals fuelling El Jadida Beach, via the Oued Oum Rbia and littoral drift, are essentially Jacqueline and Sidi Said Maachou El Jadida beach is under anthropogenic pressure considerable (proliferation of buildings) that promote the reduction of the area of the beach and therefore it creates a malfunction of this and an imbalance between it and marine and wind dynamics. Where urgent intervention and sound management that apply to the protection of this beach and its environment.